Ko opravljaš najbolj nemogočo službo na svetu - Šabič, Zlatko (Teorija in praksa, 2016)
The aim of this paper is to analyse the role and importance of the position of Secretary-General of the United Nations (UN). This article is based on the thesis that a high level of independence of the Secretary-General in formulating and implementing UN policies brings certain risks because member states, especially the permanent members of the Security Council, are unwilling to accept the role of the Secretary-General as an equal player. The lessons learned from past mandates indicate there is considerable mistrust in Secretaries-General. However, this is inconsistent with the challenges from the external environment the UN has to deal with. In the contemporary international community, which is becoming increasingly conflictual, there is a realistic need for a Secretary-General whose primary task, even at the expense of states' interests, would be to actively strengthen the role and image of the UN as an organisation whose existence is critical in any effort to prevent a new world war.
Keywords: Administrative agencies; generalni sekretarji; International organizations; Mednarodne organizacije; Mirovne operacije; Organizacija združenih narodov; Peacekeeping; Upravni organi